2010
DOI: 10.3354/dao02286
|View full text |Cite
|
Sign up to set email alerts
|

Batrachochytrium dendrobatidis infection dynamics in the Columbia spotted frog Rana luteiventris in north Idaho, USA

Abstract: The pathogenic chytrid fungus Batrachochytrium dendrobatidis (Bd) is contributing to amphibian declines worldwide. Temperature plays an important role in both pathogen growth and host immune function, but little is known about seasonal dynamics of Bd infection in north temperate regions. Our objective was to increase understanding of Bd disease ecology by investigating patterns of Bd infection of Columbia spotted frogs Rana luteiventris across seasons, age classes, and sexes in north Idaho, USA. We collected s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…We also demonstrated that the dynamics of Bd infections on L. rheocola were influenced by temperature and season, effects that have been reported in previous studies on several species in Australia and elsewhere [15,18-20,35-37]. Prevalence of Bd in adult frogs was higher in cooler than in warmer months, and was higher at higher elevations, as has been reported elsewhere [18,38,39].…”
Section: Discussionsupporting
confidence: 86%
“…We also demonstrated that the dynamics of Bd infections on L. rheocola were influenced by temperature and season, effects that have been reported in previous studies on several species in Australia and elsewhere [15,18-20,35-37]. Prevalence of Bd in adult frogs was higher in cooler than in warmer months, and was higher at higher elevations, as has been reported elsewhere [18,38,39].…”
Section: Discussionsupporting
confidence: 86%
“…Previous research has suggested higher susceptibility (greater mortality rates) to Bd in western toads A. boreas (Blaustein et al ) and wood frogs L. sylvaticus (Searle et al ), and lower susceptibility in chorus tree frogs P. regilla (Reeder et al ). Prevalence of Bd observed in Idaho populations of the Columbia spotted frog R. luteiventris was high (67.6%) in adults and low in tadpoles (4.8%) (Russell et al ). We found similar, although less extreme results of 46% (90% CI: 30.5–66.5%) in adults, 96% in juveniles (90% CI: 77.6–99.9%), and 10% (90% CI: 0.8–34.1%) in larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more zoospores would be available to spread chytridiomycosis through the populations of amphibians. In adult frogs B. dendrobatidis prevalence is highest during late summer and winter, while infection takes place from late spring to early summer (Russell et al, 2010; Sapsford et al, 2013). This coincides with the breakdown of the chytrid epidemics.…”
Section: Food Websmentioning
confidence: 99%